Tradition, child labour, religous misconception, insecurity among women and under-aged educational achievement in north-eastern geo-political zone of Nigeria - Babayo, Sulaiman Jibril (2017)
The purpose of this paper is to investigate the association between tradition, child labour, religion, and insecurity factors with the educational achievement of under-aged in the North-eastern Nigeria.Female children are denied education in contrast with their male counterparts due to tradition, religious- misconceptions. Female under-aged, as the product of the denial to education during their childhood are molded into adults without education.Using available scholarly literature, the researchers conceptually explored the factors impeding the womenfolk and the educational achievement of under-aged.The findings indicated that tradition, child labour, religious misconception, insecurity drastically affect women and the educational achievement of under-aged. Theoretically, the study contributed in literature provision on educational achievement. Methodologically, the study made contributions in filling gaps in studying insufficient literacy among women under-aged educational achievement. Practically, the ministries of education, youths development and women’s affairs can apply the result to improve the life of women and the educational achievement of under-aged in relation to tradition, child labour religious misconceptions and insecurity.